Liquid-liquid extraction: A promising alternative for inhibitors removing of pentoses fermentation - Roque, Laerti Reis; Morgado, Grazielle Patricia; Nascimento, Viviane Marcos; Ienczak, Jaciane Lutz; Rabelo, Sarita Candida (Elsevier B.V., 2019)
Dilute sulfuric acid pretreatment is effective at producing a xylose-rich hydrolysate from lignocellulosic biomasses, however inhibitory compounds, released during the processes, can affect the metabolism of fermenting microorganisms, thus reducing the biomass formation, yields and productivity. In this scenario, two approaches for hemicellulosic hydrolysate detoxification were evaluated: liquid-liquid extraction (process 1) and evaporation followed by liquid-liquid extraction (process 2), using 1-butanol, isobutyl acetate and MIBK as extractants. The hydrolysates (detoxified and non-detoxified) fermentations were evaluated by S. stipitis and S. passalidarum. Although process 1 has provided good removal efficiencies, acetic acid concentration in detoxified hydrolysate was still relatively high, while process 2 resulted in 90% of global acetic acid removal. S. passalidarum detoxified hydrolysates fermentation showed higher ethanol yields and productivities than S. stipitis. An inhibitory effect of 1-butanol has been achieved for both yeasts, resulting in low sugar consumption and consequently low ethanoltiters. Process 2 with MIBK led to 69.0% of phenolics; 85.4% of acetic acid and 100.0% of HMF and furfural extractions, with ethanol yield and productivity of 75.6% and 0.41 g/g, respectively. This process comes up as a promising method once it provides toxic-compounds removal without carbohydrates losses and allows an extractant-recycling integrated process.
Keywords: Detoxification; Liquid-liquid extraction; Furan aldehydes; Phenolic compounds; Acetic acid; Pentoses fermentation